Perfil sócio-demográfico, clínico e funcional de idosos comunitários com osteoartrite de joelhos e/ou quadris com enfoque na síndrome da fragilidade - Rita de Cassia Correa Miguel (2011)
The aging of the Brazilian population has been accompanied by alterations in its epidemiological profile. This has brought about the appearance of a new health paradigm where chronic degenerative diseases and their comorbidities have replaced infecto-contagious diseases. Studies have shown that there is an association between osteoarthritis and frailty, two conditions that are closelyassociated with aging and which, in isolation, may interfere with functional capacity, autonomy and, consequently, in the quality of life of this population.Until now, no studies have been found which characterize elderly people with osteoarthritis according to frailty phenotype. Thus, the aim of this study was to characterize and compare community-dwelling elderly people with knee and/or hip osteoarthritis according to the presence of frailty syndrome . A transversal study was carried out to evaluate socio-demographic characteristics, co-morbidity, depression, anthropomorphic data, subjective evaluations of health, falls, pain, rigidity, function and frailty in elderly subjects with osteoarthritis of the knee and hip using a subsample from FIBRA Network (a study of frailty in Brazilian elderly people).The final sample consisted of 58 elderly people with an average age of 74 (±5.5). 17 (29.31%) were classified as non-frail (NF) 28 (48.28%) as pre-frail (PF) and 13 (22.41%) as frail(F) . F groupused more drugs (7.00 ± 2.00) than NF group (4.00 ± 2.00), (p =0.001). The BMI (Body Mass Index) was lower for the elderly in NF group (average of 27.00 ±4.50 Kg/m2) compared to PF group (average of 30.00 ± 4.00 Kg/m2) and F group (average of 34.00 ± 8.00 Kg/m2), (p = 0.018). History of depression was more prevalent in frailty group. When comparing the subjects health with the situation one year before, a difference was found between the groups (p = 0.016). The majority of the elderly in PF Group (64.3%) believed that their health had deteriorated compared to 46.2% of F Group and in NF group 52.9% believed that their health was unchanged. When present levels of activity were compared with those one year before, PF and F Groups considered that the present level was worse (p = 0.010). In the case of function, it was found that FGroup was worse than the others (p = 0.023), and the same was found for fallrelated self-efficacy (p=0.017).There were no significant differences between the groups for the remainder of the items analyzed. The elderly persons with osteoarthritis and frailty use more drugs, were more obese, suffered more depression, have less fall-related self-efficacy and worse physical function, as well as a poorer perception of their own health and their level of activity in comparison with the previous year. These characteristics may have a negative impact on their quality of life and demand the attention of health professionals.